Niche Partitioning of Microbial Communities at an Ancient Vitrified Hillfort: Implications for Vitrified Radioactive Waste Disposal. Issue 1 (2nd January 2021) - Plymale, Andrew E.; Wells, Jacqueline R.; Pearce, Carolyn I.; Brislawn, Colin J.; Graham, Emily B.; Cheeke, Tanya E.; Allen, Jessica L.; Fansler, Sarah J.; Arey, Bruce W.; Bowden, Mark E.; Saunders, Danielle L.; Danna, Vincent G.; et al.
Abstract: Because microbes cannot be eliminated from radioactive waste disposal facilities, the consequences of bio-colonization must be understood. At a pre-Viking era vitrified hillfort, Broborg, Sweden, anthropogenic glass has been subjected to bio-colonization for over 1, 500 years. Broborg is used as a habitat analogue for disposed radioactive waste glass to inform how microbial processes might influence long-term glass durability. Electron microscopy and DNA sequencing of surficial material from the Broborg vitrified wall, adjacent soil, and general topsoil show that the ancient glass supports a niche microbial community of bacteria, fungi, and protists potentially involved in glass alteration. Communities associated with the vitrified wall are distinct and less diverse than soil communities. The vitrified niche of the wall and adjacent soil are dominated by lichens, lichen-associated microbes, and other epilithic, endolithic, and epigeic organisms. These organisms exhibit potential bio-corrosive properties, including silicate dissolution, extraction of essential elements, and secretion of geochemically reactive organic acids, that could be detrimental to glass durability. However, long-term biofilms can also possess a homeostatic function that could limit glass alteration. This study documents potential impacts that microbial colonization and niche partitioning can have on glass alteration, and subsequent release of radionuclides from a disposal facility for vitrified radioactive waste.